Leishmania infantum affects alternative splicing in human neutrophils infected in vitro - Zutin, Luana Araujo [UNESP] (Universidade Estadual Paulista (Unesp), 2026)
Visceral leishmaniasis, caused by Leishmania infantum, remains a major public health problem in Brazil and other endemic countries, particularly in regions marked by socioeconomic vulnerability. After infection, the parasite interacts with innate immune cells, including neutrophils, and can modulate essential molecular processes that shape the host response. Among these processes, alternative splicing stands out as a co-transcriptional mechanism that expands transcript and protein diversity from a single gene and plays a critical role in immune regulation. Although splicing alterations have been described in several infectious contexts, their effects on human neutrophils infected with L. infantum had not yet been investigated. In this study, the transcriptomes of infected and uninfected human neutrophils, obtained from healthy donors under paired conditions, were analyzed. Following RNA sequencing, quality control, alignment, transcript assembly, and quantification were performed. Alternative splicing analysis, conducted using SUPPA2, enabled the identification of differentially regulated events and isoforms between conditions, considering as significant those with inclusion changes ≥ 0.1 and p-values ≤ 0.05. Although numerous splicing events were detected in neutrophils, only a subset showed significant differences after infection, with exon skipping events being the most prevalent. At the isoform level, ten transcripts were differentially regulated, and complete isoform switching was observed in the CCM2L and SLC25A52 genes. Structural prediction of these isoforms using AlphaFold2 revealed subtle changes in SLC25A52, whereas CCM2L displayed pronounced structural and domain alterations, suggesting potential functional implications in the early response to infection. These findings indicate that L. infantum selectively modulates alternative splicing in human neutrophils, introducing an additional layer of co-transcriptional regulation that may influence parasite-host interaction dynamics.

A leishmaniose visceral, causada por Leishmania infantum, permanece como um importante problema de saúde pública no Brasil e em outros países endêmicos, especialmente em regiões caracterizadas por vulnerabilidade socioeconômica. Após a infecção, o parasito interage com células do sistema imune inato, incluindo os neutrófilos, podendo modular processos moleculares essenciais para a resposta do hospedeiro. Entre esses processos, destaca-se o splicing alternativo, um mecanismo co-transcricional que amplia a diversidade de transcritos e proteínas a partir de um único gene e desempenha papel crítico na regulação da imunidade. Embora alterações de splicing já tenham sido descritas em diferentes contextos infecciosos, seus efeitos em neutrófilos humanos infectados por L. infantum ainda não haviam sido investigados. Neste estudo, analisou-se o transcriptoma de neutrófilos humanos infectados e não infectados, obtidos de doadores saudáveis em condições pareadas. Após o sequenciamento de RNA, foram realizados controle de qualidade, alinhamento, montagem e quantificação dos transcritos. A análise de splicing alternativo, conduzida por meio da ferramenta SUPPA2, permitiu identificar eventos e isoformas diferencialmente regulados entre as condições avaliadas, considerando como significativos os eventos com variações de inclusão iguais ou superiores a 0,1 e valores de p inferiores ou iguais a 0,05. Embora numerosos eventos de splicing tenham sido detectados nos neutrófilos, apenas uma fração apresentou diferenças significativas após a infecção, com predominância de eventos de exclusão de éxons. No nível de isoformas, dez transcritos foram diferencialmente regulados, sendo observada troca completa de isoformas nos genes CCM2L e SLC25A52. A predição estrutural dessas isoformas por meio do AlphaFold2 revelou alterações sutis em SLC25A52, enquanto CCM2L apresentou modificações estruturais marcantes, sugerindo possíveis implicações funcionais na resposta inicial à infecção. Esses achados indicam que L. infantum modula o splicing alternativo de forma seletiva em neutrófilos humanos, introduzindo uma camada adicional de regulação co-transcricional que pode influenciar a dinâmica da interação parasito-hospedeiro.
Leishmania infantum afeta o splicing alternativo em neutrófilos humanos infectados in vitro
Keywords: Splicing alternativo; Neutrófilos; Leishmania infantum; Transcriptômica; Isoformas; Alternative splicing; Neutrophils; Transcriptomics; Isoforms